Método sencillo para determinar la presencia de Toxoplasma gondii (Eucoccidia: Sarcocystidae) en carne - Chinchilla, Misael (Universidad de Costa Rica, 1997)
Presence of T. gondii in meat from several sources was deterrnined by traditional methods and by a new simplified method in which animals are fed meat directly without any previous treatment with artificial gastric fluid. Tissues are ground and the animals ingest them naturally. Deterrnination of Toxoplasma in lungs or brain (as well as by specific antibody test), showed no statistically significant differences between both methods.